Creation of the "Berezivskyi" landscape reserve of local importance as a component of preservation of natural landscapes, biotopes and species diversity of the Northeast of Ukraine - Bezrodnova, O.V.; Bondarenko, Z.S.; Brusentsova, N.O.; Ivanova, K.Yu. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2024)
In the process of creating the "Berezivskyi" landscape reserve, surveys were conducted on xerophytic, meadow, and waterlogged habitats located on the slopes and the floor of a ravine. The ravine belongs to the basin of the Merla River. The proposed reserve area is situated in northern Kharkiv Oblast near the village of Berezivka, within the Krasnokutsk territorial community in Bohodukhiv District. Remnants of steppe ecosystems that once dominated this area have survived on the upper slopes but have been affected by human activity and are now primarily used for agriculture. The floristic diversity of the xerophytic vegetation averages 23-26 vascular plant species per 100 m², with some patches supporting up to 40 species. These areas hold phytocoenotic value due to the presence of state-protected plant species, including Adonis vernalis L., Colchicum bulbocodium Ker Gawl., Crocus reticulatus Steven ex Adams, Pulsatilla pratensis (L.) Mill. s.l., and Stipa capillata L. The proposed reserve is also significant for the conservation of Marmota bobak (Müller, 1776), a species listed in Ukraine’s Red Data Book in 2021. A small stream flows along the ravine floor, partially dammed by Castor fiber L., with its lower reaches connected to an artificial pond. These water bodies provide vital habitats for breeding amphibians such as Lissotriton vulgaris (Linnaeus, 1758), Pelopylax ridibunda (Pallas, 1771), Rana arvalis (Nilsson, 1842), Bufotes viridis (Laurenti, 1768), Pelobates vespertinus (Lichtenstein, 1823), and Bombina bombina (Linnaeus, 1758). Additionally, a large population of Lacerta agilis (Linnaeus, 1758) inhabits the ravine slopes, with Natrix natrix (Linnaeus, 1758) encountered along the stream banks. All these amphibian and reptile species are included in the appendices of the Bern Convention. The landscape and phytocoenotic diversity within the proposed reserve contribute to a diverse avifauna and entomofauna. Eighteen bird species have been identified to date; though common to Kharkiv Oblast, they require protection under the Bern Convention. One bird species, Grus grus (Linnaeus, 1758), is protected at the national level. Additionally, two insect species listed in Ukraine’s Red Data Book, Xylocopa valga (Linnaeus, 1767) and Hamearis lucina (Linnaeus, 1758), have been recorded, though further studies of the entomofauna are necessary. The primary goal of the proposed reserve is to conserve landscapes typical of the Ukrainian Forest-Steppe, particularly remnant steppe ecosystems, as habitats for rare and endangered species protected at regional, national, and pan-European levels. Another important objective is the restoration of herbaceous biotopes that have experienced heavy grazing impacts in the past, mainly along the ravine floor and lower gentle slopes. The area has additional conservation value because, at the time of writing, it has remained unaffected by the destructive impacts of ongoing hostilities.